Estudio de prefactibilidad para la instalación de una planta productora de suplementos nutricionales a base de hojas de moringa en cápsulas - Lazaro Cubas, Miguel Junior (2020)
The objective of this thesis is to determinate the market, technological, financial and social viability for the implementation of an industrial producing plantsupplements based on moringa, which will provide a solution to the problem of malnutrition suffered by pregnant women of Metropolitan Lima. From the market point of view, the first thing that was determined was that the target market would be women aged 18 to 45 years of socioeconomic levels B, C and D of Metropolitan Lima who are in gestation or lactation period. Analyzing the aforementioned market and the results of the survey, the annual demand for bottles of 120 moringa capsules for the fifth year of the project would be 56,139 bottles. In the evaluation of the engineering of the project, it was determined that a semi automatic production process would be used and the minimum area of production would be 33 m2, this was calculated using the Guerchet method. Considering all the necessary areas in the industrial premises, a plot of 600m2 was defined. In the financial analysis, it was determined that an investment of S/ 873,921 was needed, which would be financed 60% with the help of a bank loan at a rate of 15% and the remaining 40% with contribution from shareholders at a rate of 18% (COK). With this a financial IRR of 69% is obtained, together with a financial NPV of S / 1,138,663, benefit / cost ratio of 1.14 and recovery period of 2 years 11 months, positive indicators in the eyes of any investor. Finally, in the social evaluation it was concluded that the project was beneficial because it generated an added value of S/ 4,619,436 at present value and other positive social indicators.